Physicochemical Properties of the Microbial Exopolysaccharide Ethapolan Synthesized on a Mixture of Growth Substrates - Pirog, Tatiana; Kovalenko, M.; Kuzminska, Yu.; Votselko, S. (My University, 2004)
Some physicochemical properties of the microbial exopolysaccharide (EPS) ethapolan synthesized by Acinetobacter sp. 12S depended on whether the producer was grown on a mixture of ethanol and glucose or on a single substrate. Irrespective of the carbon source in the nutrient medium, the contents of carbohydrates, pyruvic acid, uronic acids, and mineral components in the EPS remained unchanged. The EPS were also identical in their monosaccharide composition: the molar ratio of glucose, mannose, galactose, and rhamnose was 3 : 2 : 1 : 1. EPS with a higher content of fatty acids was synthesized during growth on the mixture of ethanol and glucose. The average molecular mass and the content of high-molecular (M > 2 MDa) fractions were greater in ethapolan produced on the substrate mixture. In the presence of 0.1 M KCl, after transformation into the H+ form, and in the Cu2+–glycine system, solutions of these EPS showed higher viscosity than solutions of EPS synthesized on single substrates. The reasons for the improved rheological properties of the EPS produced on the substrate mixture are discussed.

Вивчені фізико-хімічні властивості мікробного екзополісахариду (ЕПС) етаполану, синтезованого при вирощуванні продуцента Acinetobacter sp.12S на суміші етанолу і глюкози, а також на моносубстратах. Встановлено, що незалежно від природи джерела вуглецевого живлення ЕПС характеризувалися однаковим змістом у їх складі вуглеводів, піровиноградної, уронових кислот і мінеральних компонентів. Досліджувані ЕПС були ідентичні також за моносахаридних складом: молярне співвідношення глюкози, манози, галактози і рамнози становило 3:2:1:1. При культивуванні продуцента на суміші субстратів синтезировался ЕПС з більш високим вмістом жирних кислот, ніж на моносубстратах. Середня молекулярна маса, а також вміст у ЕПС високомолекулярних фракцій (більше 2 млн.) було вище у етаполану, отриманого на суміші етанолу і глюкози. Розчини такого ЕПС характеризувалися більш високою в'язкістю в присутності 0,1 М КСl, при перекладі в Н +-форму і системі Cu2 +-гліцин, ніж ЕПС, синтезовані на моносубстратах. Обговорюються причини поліпшення реологічних властивостей ЕПС, отриманого на змішаному субстраті.
Keywords: exopolysaccharides; cultivation conditions; substrate mixture; chemical composition; molecular mass; rheological properties; екзополісахариди; умови культивування; змішаний субстрат; хімічний склад; молекулярна маса; реологічні властивості; кафедра біотехнології і мікробіології